Effect of drying methods and packaging materials on quality parameters of stored kokum rind - Hande, A R; Swami, Shrikant Baslingappa; Thakor, N J (International Journal of Agricultural and Biological Engineering, 2014)
Abstract: In this paper kokum rind dried by different methods, i.e. open air sun drying, solar drying and the convective hot air drying (60oC) was taken after being packed in gunny bags, nylon bags and plastic jars for storage study upto nine months. The effect of different drying methods on quality parameters i.e. acidity, pH, TSS, reducing sugar, non-reducing sugar, colour (L, a and b) and calorific value of the stored product were evaluated. The quality parameters were tested at three-month intervals. Among three packaging materials, plastic jar was found best for kokum rind storage upto nine months as compared with nylon and gunny bags. Deterioration occurred as changes in acidity, non-reducing sugar, lightness, redness and calorific value over the storage period from the 0th to the 9th month. However, the TSS and b value increased as storage duration extended.Keywords: kokum rind, storage, drying methods, packaging materials, quality evaluationDOI: 10.3965/j.ijabe.20140704.013Citation: Hande A R, Swami S B, Thakor N J. Effect of drying methods and packaging materials on quality parameters of stored kokum rind. Int J Agric & Biol Eng, 2014; 7(4): 114-126.